1987 : year of rededication to liberation / [mensaje del presidente Sam Nujoma dirigido al pueblo de Namibia el 31 de diciembre de 1986]
Tít. tomado de la cub.En la cub.: What is it that we have not yet done and must do to bring about the much longed for day of liberation?